An Improved Best Estimate Plus Uncertainty Method for Small-Break Loss-of-Coolant Accident in Pressurized Water Reactor - Sun, Dabin; Zhang, Zhijian; Li, Xinyu; Li, Lei; Wang, He; Xu, Anqi; Chen, Sijuan (Frontiers in Energy Research, 2020)
Best-Estimate plus uncertainty analysis (BEPU) method has been widely used to analyze various transient accident of PWR. However, the traditional BEPU method has some limitations: 1) The input parameters are not clearly defined, resulting in inaccurate conclusions in the sensitivity analysis. 2) The Uncertainty quantification and sensitivity analysis usually share the same set of samples, but they have different requirements for the sample size. In this work, an improved BEPU method is proposed, which can alleviate the above defects. The improved BEPU method possesses the following two characteristics: 1) The sensitivity analysis is performed for the steady-state and transient calculation, respectively. It provides more comprehensive results compared to the traditional BEPU method. 2) The sensitivity analysis is performed before the uncertainty analysis to reduce the number of uncertainty analysis inputs. An SBLOCA is simulated by RELAP5 to verify the accuracy and applicability of the improved BEPU method. By the sensitivity analysis, the coolant pump inlet roughness, main flow rate, core heat channel temperature, break area and PRZ pressure have moderate or higher relationships with the peak core outlet temperature. The fission product yield factor has a moderate positive relationship with the peak cladding temperature. The sensitivity analysis by the improved BEPU method shows that the peak core outlet temperature have strong relationships with main flow rate, core heat channel temperature and PRZ pressure, which is not captured by the traditional BEPU method. As a result, it is more reasonable to take steady-state parameters as inputs in the sensitivity analysis of transient. Only those parameters with high correlation coefficients are sampled for uncertainty analysis. Meanwhile, the results of the uncertainty analysis obtained by improved BEPU are consistent with the results of the traditional method. Neither the PCT nor the peak core outlet temperature will exceed their limits. The results illustrate that the improved BEPU method can reduce the size of samples and maintains the desired accuracy.